The Effect of Plant Downsizing on Disability Pension Utilization - Kjetil Telle Mari Rege; Mark Votruba (Statistics Norway, Research Department, 2005)
We investigate the impact of plant downsizing on disability pension utilization in Norway. Plant downsizing substantially increases the disability entry rate of workers in affected plants. Workers originally employed in plants that closed between 1993 and 1998 were 27.9 percent more likely to utilize disability pensions in 1999 than comparable workers in non-downsizing plants. The effect of downsizing is non-linear, with workers originally employed in plants downsizing 65-95 percent of their workforce more likely to enter disability than workers in fully closing plants. This is consistent with the signaling story of Gibbons and Katz (1991). We also estimate significant effects of downsizing on future earnings and mortality, suggesting the increase in disability participation could be driven by an adverse effect of downsizing on the economic opportunities or health of affected workers
Keywords: H55; I12; I38; J63; J65; 330; disability; social insurance; downsizing; layoffs; plant closings